PENINGKATAN KETERAMPILAN MENULIS PUISI PADA MURID KELAS 10 SMK NEGERI 3 SURABAYA DENGAN MODEL PEMBELAJARAN COOPERATIVE INTEGRATED READING (CIRC) - Lisa Kusuma Aprilia; Khoirul Anam; Imam Hidayatulloh; Indira Rizkia Intan Nabilla; Kholifatur Riski Amalia; Lailatul Badriyah; Sunu Catur Budiyono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The ability to write poetry is one of the important competencies in Indonesian language learning because it plays a role in developing creativity, emotional sensitivity, and students' ability to express themselves. However, the poetry writing skills of class X TPM 3 students of SMK Negeri 3 Surabaya are still relatively low, as indicated by 53% of students obtaining scores below the Minimum Completion Criteria (KKM) of 75 in the pre-action stage. This study aims to improve poetry writing skills through the application of the Cooperative Integrated Reading and Composition (CIRC) learning model based on Problem Based Learning (PBL). The study used the Classroom Action Research (CAR) method with a quantitative approach implemented in two cycles. The research subjects were 30 class X TPM 3 students of SMK Negeri 3 Surabaya. Data collection techniques were carried out through observation and poetry writing skills tests in each learning cycle. The results of the study showed that the application of the CIRC model was able to improve students' poetry writing skills gradually. At the end of cycle I, the percentage of learning completion increased to 60%, while at the end of cycle II it increased to 80% of students who had achieved the KKM. This improvement was supported by group discussion activities, providing poetry examples, peer feedback, and a collaborative process in developing ideas. Furthermore, critical thinking skills and social interactions among students also contributed to improving the quality of the poetry produced. Thus, the CIRC learning model based on Problem Based Learning has proven effective in improving the poetry writing skills of class X TPM 3 students at SMK Negeri 3 Surabaya.